KARAKTER DALAM PREMAN, ANTOLOGI CERKAK KARYA TIWIEK SA DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA JAWA - Purboasri, Galih Dwi; Saddhono, Kundharu; Suyitno, Suyitno (Center of Language and Cultural Studies, 2017)
This study analyzed characters of Preman, an anthology of short story written by an outstdanding Javanese author, Tiwiek SA and its implication to teaching Javanese for secondary school students. The analyses focused on characterization, theme and title of the short story pertaining. Structural anaysis was used in this study as research design. Primary data of this study were 6 text of Javanese short story written in anthology entitled Preman. Secondary data include result of interview to the author. The study revealed that characters reflected Javanese society. Themes of the shortstory attracted the readers to read the contents as the interesting issues. The titles of the short story implicated that indigenous Javanese native speakers can improve and maintain Javanese culture and sociolinguistics. Accordingly, the short story contributes substantial effects on teaching Javanese for secondary school students from which teaching materials and authentic data are derived.